1982
DOI: 10.1007/bf02411291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of parathyroid hormone and calcium ionophore A23187 effects on bone resorption and nucleic acid synthesis in cultured fetal rat bone

Abstract: It has recently been demonstrated that calcium ionophore A23187 mimics certain of the effects of parathyroid hormone (PTH) on bone in vitro, including stimulation of 45Ca release and cAMP formation. To further examine the relative effects of these two agents on bone cell metabolism, we compared the effects of synthetic PTH 1-34 (50 ng/ml) and calcium ionophore A23187 (0.5 micrograms/ml) on 45Ca release, DNA concentration, and nucleic acid synthesis in fetal rat forelimb rudiments cultured for periods up to 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Our data suggest that functional PTH receptors, likely through affecting proliferation or apoptosis, contribute to the increase of mesenchymal cell numbers. These results agree with studies reporting that PTH stimulates osteoblast proliferation (2,4) and increases osteoblast number (44) and that a constitutively active PTH-1R increases osteoblast number in trabecular bone in transgenic mice (15). Additionally, Watson et al (45) suggest that the PTH-1R localizes to the nucleus and may be associated with ligand-independent proliferation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data suggest that functional PTH receptors, likely through affecting proliferation or apoptosis, contribute to the increase of mesenchymal cell numbers. These results agree with studies reporting that PTH stimulates osteoblast proliferation (2,4) and increases osteoblast number (44) and that a constitutively active PTH-1R increases osteoblast number in trabecular bone in transgenic mice (15). Additionally, Watson et al (45) suggest that the PTH-1R localizes to the nucleus and may be associated with ligand-independent proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanisms underlying the PTH anabolic effect in bone are not fully understood. The increased bone formation has been attributed to activation of growth factors (2,3), osteoblast precursor cell proliferation (2,4), and mature osteoblast function (2). Recent studies suggest that suppression of osteoblast apoptosis might play a major role in PTH anabolic action (5); however, the impact of cell differentiation and the pathways operating in this process have not been well characterized.…”
mentioning
confidence: 99%
“…Parathyroid hormone (PTH)' is an important stimulator of bone resorption both in vivo and in vitro, and increases the number of osteoclasts in bone (8)(9)(10). PTH also increases DNA synthesis in bone cells (2,11,12,13). However, definitive evidence demonstrating that the cells that replicate in response to PTH also differentiate into osteoclast precursor cells is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the culture systems, animal models, and experimental conditions, different studies have shown variable results with respect to the anabolic effect of PTH as it relates to osteoblast proliferation. For instance, in vitro organ cultures of embryonic mouse radii and rat calvarie showed that PTH increases osteoblast number (15) and stimulates osteoblast replication (5,8) but decreases the collagen synthesis (10,40). PTH stimulated cell proliferation in cultures of the human osteosarcoma cell line TE-85 (12,30); however, it inhibited cell proliferation in UMR-106 osteosarcoma cell cultures (33).…”
mentioning
confidence: 97%